Sekular, Tradisionalis, dan Modernis (Sejarah, Karakteristik, dan Refleksinya di Indonesia) - Vicky Izza El Rahma (STAI Syaichona Moh. Cholil Bangkalan, 2017)
Religion in contemporary religious discourse emerge with many faces (multifaces). Religion is no longer just a problem exclusively associated with divinity, faith, way of life, and so on. Each of the secular ideology, traditionalists and modernists has its own positive and negative sides; traditionalist ideology which is actually quite rich with a variety of classical Islamic thought, but rather with the wealth of the proponents of this idea is strongly oriented to the past and are very selective accept the ideas of modernization; so did the Islamic modernists who tend to show itself as a flexible thinking and, further, developing the liberal tendencies. Responding to this, the contemporary Islamic thinkers initiated a new movement known as post-traditionalism and postmodernism. Ideology as a definition of the concept of applying the principle of opinion made give direction and purpose to the survival of a true movement is tentative. That is a movement, which in the past considered a traditionalist ideology; very likely at present to change course on the ideology of post-traditionalism, modernism, post-modernism, or even secular. The same thing passes versa.